Epidemiological and Molecular Characterisation of Citrus Huanglongbing (HLB) Disease in Malaysia - Ahmad, Khairulmazmi (2008)
Citrus huanglongbing (HLB) disease is considered as one of the most destructive diseases of citrus in Asian, African and American countries. It is caused by Candidatus Liberibacter species. In Asian countries, the causal agent is Candidatus Liberibacter asiaticus. Surveys of the HLB disease on infected citrus trees were carried out in the major citrus growing areas in Peninsular Malaysia namely Selangor, Pahang, Kelantan and Pahang. The occurrence of HLB disease was confirmed by polymerase chain reaction (PCR) and transmission electron microscope (TEM) tests. Candidatus Liberibacter asiaticus was detected positive in samples collected from honey mandarin (Citrus reticulata), pummelo (C. grandis), Mexican lime (C. aurantifolia), mandarin (C. suhueinsis), calamondin (C. madurensis), Cleopatra (C. reticulata), Troyer citrange (Poncirus trifolia X C. sinensis) and citrirnelo (P. trifolia X C. paradise). Field-infected citrus trees showed typical symptoms of HLB disease such as intervienal chlorosis, green vein, dieback of twigs, lopsided fruit shape, small fruit size and premature fruit drop easily. All the major citrus growing areas in Peninsular Malaysia were found infected with HLB disease. The percentage mean estimate disease incidence ranged from 28.3 - 53.8% and 0.0 - 46.03% depending on localities and citrus species, respectively. The seriousness of the disease justified further studies on the epidemiology and molecular characterization of the causal agent, Candidatus Liberibacter asiaticus in Malaysia. HLB vector, Diaphorina citri were more abundant in the lowland areas such as Selangor and Terengganu. It was absence in Cameron Highland, Pahang but moderate level was recorded in Lojing Highland, Kelantan. Further study on characterization and strain differentiation of Malaysian Candidatus Liberibacter asiaticus isolates was carried out. Based on their biological (pathological) properties, Malaysian isolates exhibited six types of HLB symptoms such as olive green of leaves, green vein, vein yellowing, mottling, stunted and dieback of twigs. In terms of disease incidence and disease severity reactions, Malaysian isolates showed sigmoid pattern of disease progress curves and caused polycyclic type of disease. Based on their aggressiveness, Malaysian isolates could be classified into three groups i.e. severe, moderate and mild. In terms of molecular properties, all isolates produced intense accumulation of starch granule inside the tissue of infected leaves. TEM study revealed that Malaysian isolates were pleomorphic and consisted of two types of bodies i.e. elongated and spherical forms. The body lengths ranged from 100-1200 nm depending on their body shape and the isolates. Differentiation of their modal length and composition ratio revealed that the Malaysian isolates could be classified into two groups i.e. group 1 comprises of GFB-T and GFB-S and group 2 comprises of GFB-PK. Characterization of their 16s rDNA gene sequences revealed that Malaysian isolates produced about 1 156-1 167b.p of nucleotide sequences. Gene sequences between Malaysian isolates showed high percentage of nucleotide similarity that ranged from 96-99%. Similar trends were observed on their genetic distances. Analysis of outer membrane protein (OMP) gene also showed differences between Malaysian isolates tested, namely GFB-Mandarin and GFB-Pummelo. A study on host preference of D. citri and susceptibility of citrus species against GFB-T isolate indicated that D. citri most preferred to colonize and feed on jasmine orange (Munaya paniculata) followed by sour orange (C. aurantium), pummelo and honey mandarin. Host susceptibility study revealed that jasmine orange and pummelo were resistant to HLB infection while sour orange was found to be tolerant. Calamondin was susceptible and honey mandarin was very susceptible to HLB infection. The effect of calcium, zinc and copper application on plants' recovery and severity following infection of HLB disease showed slight protection against the HLB bacterium but was inconsistent in some cases. Citrus trees treated with combination of calcium and zinc at 600 ppm, and 10 ppm respectively resulted to significant increase (P10.05) in terms of fruit production and total soluble solid (TSS) content. This treatment also resulted in reduction of AUDPC value of disease severity and also improved mean leaf length, mean leaf width and mean leaf area. To date, there is no successful treatment available throughout the world including Malaysia to control HLB disease in the orchards. Perhaps the combination of present treatment together with good agriculture practices could improve the efficiency of HLB management in the orchards by enhancing tree immunity, delaying disease onset to prolong lifespan of citrus trees.